The effect of leadership styles on reducing social loafing: An exploratory study of the opinions of a sample of employees in the Administrative Technical College / Kufa - Abbas Hassan, Fadhil; Wasan Jawad Kadhim (Iraqi Journal for Administrative Sciences, 2024)
The research aims to reveal the impact of leadership styles through their dimensions in reducing cases of social loafing based on the answers of a sample of workers in the Administrative Technical College / Kufa. Which the organization may be exposed to during its life cycle represented in (indifference, disruptive behavior, interruption of work, and decreased effort), the research is based on the main hypothesis that (there is a significant impact of leadership styles in reducing the phenomenon of social loafing ). To achieve the objectives of the research, a questionnaire consisting of (32) items was designed and distributed to a sample of (70) employees, of which (62)questionnaire are valid for statistical analysis. The research also reached several results, the most important of which is that the Administrative Technical College in Kufa, represented by its leadership, adopts a supportive leadership style mainly to reduce the phenomenon of social loafing , and the research also came out with several recommendations